Research on the learning experience of virtual simulation class experimental teaching and learning based on the perspective of nursing students - Gao, Yazhuo; Zhu, Xuehua (BMC nursing, 2023)
Background The enrichment of information technology has impacted traditional teaching modes. The emergence of virtual simulation class experimental teaching software has effectively improved the quality of nursing experiment teaching. The learning experience of virtual simulation class experiment teaching and learning based on the perspective of nursing students is explored to provide a basis for improving related learning effects in the future. Methods Fourteen undergraduate nursing students were selected using the purposive sampling method for semi-structured interviews. The Colaizzi seven-step analysis method was used to collate and analyse the interview data. Results Two themes and six sub-themes were considered during the data analysis. The two themes were positive experiences and negative experiences. In the positive learning experience, undergraduate nursing students showed a deep memory of authentic and diverse scenes, which presented knowledge in a clearly logical, visualised and stereoscopic manner. Negative experiences are manifested as significantly different learning efficiencies in different grades and subjects, and timing the delivery of teaching feedback is difficult. Conclusion Virtual simulation experimental teaching can promote the subjective initiative of nursing students’ learning and promote better coordination and unity in their image and theoretical thinking. Some advantages can be augmented by following the national educational policy, strengthening the information construction, combining the construction of virtual simulation experiments with the discipline’s characteristics and optimising the resources. This paper provides a reference for the future exploration of nursing education and further improving the construction of virtual simulation experimental teaching tools and resources.